Penafsiran Shalat Wustha Dalam Surah Al Baqarah Ayat 238 (Studi Komparatif Tafsir Al-Qurtubi dan Al-Mishbah) - Gitra Yono (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study examines the interpretation of Shalat Wustha in Surah Al-Baqarah verse 238 as a specific command to maintain obligatory prayers, which are often neglected by modern Muslims, especially Shalat Ashar. The main objective is to comparatively analyze the interpretation of Shalat Wustha between Tafsir Al-Qurtubi (classical, fiqhi style) and Tafsir Al-Mishbah by M. Quraish Shihab (modern, adabi-ijtima'i style). The methods used are comparative interpretation and descriptive qualitative literature study, analyzing tafsir literature, hadith, and scientific works. The results show significant differences: Al-Qurtubi explicitly interprets Shalat Wustha as Shalat Ashar, based on authentic hadiths (such as the accounts of Ali bin Abi Talib and Ibn Mas'ud) and the authority of the majority of scholars. In contrast, M. Quraish Shihab tends to interpret it as Maghrib prayer, considering linguistic and sociological aspects, as well as its middle position (number of rakats, timing, and method of performing jahr-sir).